REVIEW: OPTIMASI PLASTICIZER UNTUK PENINGKATAN KINERJA BIOPLASTIK BERBASIS KITOSAN: REVIEW: OPTIMASI PLASTICIZER UNTUK PENINGKATAN KINERJA BIOPLASTIK BERBASIS KITOSAN - Winaryo, Ayu Pupu (Program Studi Teknik Mesin, Universitas 17 Agustus 1945 Surabaya, 2025)
Plastic waste is one of the biggest environmental issues in the modern world, due to the nature of conventional plastics that are difficult to decompose. This study reviews the potential for making biodegradable plastics from various combinations of chitosan from shrimp shell waste with other materials. This combination aims to improve the mechanical properties, biodegradability, and moisture resistance of plastics. The literature review method is used to identify the best formulation through analysis of materials, methods, and test results from various studies. The study showed the best test results in a combination of chitin and glycerol which had a tensile strength value of 38 Mpa, % elongation of 30%, and a degradation time of 25 days. The results show that chitosan is able to increase tensile strength and accelerate plastic biodegradation. Challenges such as low plastic flexibility still require formulation optimization, including the addition of plasticizers from glycerol. This study provides a comprehensive insight into the potential of bioplastics based on local Indonesian resources as an alternative to conventional plastics.